ANALISIS KEPUTUSAN KONSUMEN DALAM PEMBELIAN JAGUNG BAKAR DI KOTA PEKANBARU - Taurusandika, Wage; Maharani, Evy; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to: 1) Identify and analyze the factors that effect the decision of consumers in purchase roasted corn in the City of Pekanbaru. 2) Analyze the most decision of consumer in purchasing roasted corn in the City of Pekanbaru. The research carried out in sales location roasted corn in the City of Pekanbaru, namely in Taman Labuai or Bandar Serai Purna MTQ, Siak River Side, Naga Sakti Street, Arifin Achmad Street, H.R. Subrantas Street, Air Hitam Street. The research carried out in December 2013 to the month of June 2015. The research carried out by survey methods and sampling as many as 72 respondents. Analysis of data using the Scale's Likert Summated Ratting (SLR). The result showed that factors and psychological factors influence for consumers in purchasing roasted corn in the City of Pekanbaru, and the most dominant factors that consumers decision in purchasing roasted corn in the City of Pekanbaru with indicators that include motivation, perception, knowledge, beliefs and attitudes shown with a score 3.86. Factors that do not affect consumer purchasing decisions roasted corn in the City of Pekanbaru are cultural factors and social factors. Keywords : Consumer Decision, Purchase, Roasted Corn.